Perancangan Kemasan Permen Magic Lollipop Menggunakan Adobe Photoshop CS2 - Ratna Sumirat Putri Wiedarti; Sutarno Sutarno (Jurnal Sistem Informasi, 2010)
The development of this technology are very advanced now so rapid, resultingin most of the changes the pattern of human life evolved into a more moderndirection so that more effective and efficient. One of the advances in technologysuch as computers that help shape the development of digital imagemanipulation. Digital image manipulation has contributed so much to theworld of photography by allowing the manipulation of the initially difficult oreven impossible. One of the software that plays a major role in the developmentof today's digital world is Adobe Photoshop CS2.